Comment on García-Erce et al. Iron Deficiency and Oral Treatments: Limitations, Pharmacokinetics, and the Role of Iron Protein Succinylate in Clinical Practice. J. Clin. Med. 2026, 15, 3691 - Germano Tarantino; Maria Sole Rossato; Camilla Vullo; Elisa Brilli (Journal of Clinical Medicine, 2026)
The purpose of this letter is to comment on the review titled “Iron Deficiency and Oral Treatments: Limitations, Pharmacokinetics, and the Role of Iron Protein Succinylate in Clinical Practice” by García-Erce et al [...]